The Influence of Transformational Leadership Style and Work Discipline on Employee Performance through Work Stress at PT Sulawesi Jaya Metalindo - Gustria Emanuela; Maat Pono; Nurdjanah Hamid (Jurnal Mirai Management, 2023)
This study aims to analyze the Effect of Transformational Leadership Style and Work Discipline on Employee Performance through Work Stress at PT Sulawesi Jaya Metalindo. The population in this study is employees of PT Sulawesi Jaya Metalindo which amounts to 46 employees. The sample in this study is all employees who are the population of this study or commonly referred to as saturated samples. Data collection techniques were used by distributing questionnaires. The data analysis technique used is path analysis. The results of this study show that (1) Transformational leadership style has a negative and significant effect on work stress at PT Sulawesi Jaya Metalindo. (2) Work discipline has a negative but not significant effect on work stress at PT Sulawesi Jaya Metalindo. (3) Transformational leadership style positively and negatively affects performance at PT Sulawesi Jaya Metalindo. (4) Work discipline has a positive and significant effect on performance at PT Sulawesi Jaya Metalindo. (5) Work stress has a negative but insignificant effect on PT Sulawesi Jaya Metalindo’s performance. (6) Transformational Leadership Style through work stress as an intervening variable has a positive but not significant effect on performance at PT Sulawesi Jaya Metalindo. (7) Work discipline through work stress as an intervening variable has a positive but not significant effect on performance at PT Sulawesi Jaya Metalindo. Keywords: Transformational Leadership Style, Work Discipline, Employee Performance, and Work Stress